Insights into labour and economic dynamics in OECD countries: a non-parametric causal analysis using transfer entropy - Nur Layali Mohd Ali Khan; Saiful Izzuan Hussain (Penerbit Universiti Kebangsaan Malaysia, 2025)
The eighth goal of the global sustainable development agenda emphasises the role of the labour market as a driver of economic growth. However, the complex relationships between these elements still need to be discussed. In this study, a novel approach, called transfer entropy, is applied to analyse the causal relationships between real gross domestic product (GDP), employment, and unemployment across 38 OECD countries spanning the period of the third quarter of 2011 to the second quarter of 2023. A rigorous transfer entropy framework allows us to examine the directional flow of information between three pairs of variables: real GDP and employment, real GDP and unemployment, and employment and unemployment. The study shows that the causal relationships vary across OECD countries. The results from 38 OECD member countries improve the understanding of the reciprocal relationship between labour and output and discuss the role of fiscal and monetary policy in these cycles. The study contributes to the existing literature by offering a distribution-free statistical analysis approach to examine causality in real data and provide guidance to policymakers and businesses in designing strategic policies for sustainable economic development at national and regional levels.